Draft Annual Plan 1980-81 Part-II Union Territory of Delhi - Planning Commission (Planning Commission, 1979)
Union Terrltory Of Delhi Draft Annual Plan 1980-81 Draft Annual Plan 1980-81 Development Schemes/Protects Outlay & Expenditure Draft Annual Plan 1980-81 Targets Of Production - Physical Achievements Draft Annual Plan 1930-80 Flood Control Projcets-Targets And Achievements.
Planning Department Delhi Administration